2015
DOI: 10.1091/mbc.e15-07-0487
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylserine translocation at the yeasttrans-Golgi network regulates protein sorting into exocytic vesicles

Abstract: Protein sorting into exocytic vesicles at the yeast trans-Golgi network is believed to be mediated by their coalescence with specific lipids, but how this event is regulated is poorly understood. It is shown that phosphatidylserine flip by Drs2 is required for efficient sorting of the plasma membrane proteins Pma1 and Can1 into exocytic vesicles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(65 citation statements)
references
References 86 publications
(117 reference statements)
2
63
0
Order By: Relevance
“…0.1 A 600 eq of cell lysate was subjected to SDS-gel electrophoresis. Western blotting analysis was performed using anti-GFP antibody (1:2000) (57) to distinguish between cleaved GFP (26 kDa) and intact GFP-tagged Rer1 (40 kDa). For quantitation, membranes were scanned at 800 nm using the Odyssey Infrared Imaging System; median GFP intensities were quantified using Odyssey software (LI-COR Biosciences).…”
Section: Neo1 Influences Plasma Membrane Asymmetrymentioning
confidence: 99%
See 1 more Smart Citation
“…0.1 A 600 eq of cell lysate was subjected to SDS-gel electrophoresis. Western blotting analysis was performed using anti-GFP antibody (1:2000) (57) to distinguish between cleaved GFP (26 kDa) and intact GFP-tagged Rer1 (40 kDa). For quantitation, membranes were scanned at 800 nm using the Odyssey Infrared Imaging System; median GFP intensities were quantified using Odyssey software (LI-COR Biosciences).…”
Section: Neo1 Influences Plasma Membrane Asymmetrymentioning
confidence: 99%
“…Subcellular Fractionation-Cell lysates were analyzed by subcellular fractionation as described previously (57). Seven fractions in total were collected from the top of the sucrose gradient.…”
Section: Neo1 Influences Plasma Membrane Asymmetrymentioning
confidence: 99%
“…Hankins and collaborators have demonstrated that the plasma membrane proteins Pmal and Canl were missorted to vacuoles in S. cerevisiae drs2A cells [34], indicating that lipid flippases may play a role in sorting specific cargoes into vesicles. In our study, the morphological analysis of aptl Δ cells by TEM demonstrates that lack of Aptl resulted in abnormal organization of endomembranes in C. neoformans.…”
Section: Discussionmentioning
confidence: 99%
“…Jointly, the studies on Osh4p and OSBP suggest how sterols can be enriched directly at the trans-Golgi and why these proteins contribute significantly to the profound lipid reorganization that occurs in this compartment and beyond [12,22]. Interestingly, lipidomic analysis in yeast indicates that the percentage of sterol increases from 10 to 20 % between the trans-Golgi and the Golgi-derived exocytic vesicles [23], suggesting that these vesicles are sterol conveyors and contribute to sterol build-up in the PM.…”
Section: Using a Ptdins(4)p Gradient To Create A Sterol Gradientmentioning
confidence: 99%